2009
DOI: 10.1088/0741-3335/51/5/055002
|View full text |Cite
|
Sign up to set email alerts
|

Thomson scattering system on the TEXTOR tokamak using a multi-pass laser beam configuration

Abstract: The main challenge for the Thomson scattering (TS) diagnostic on the TEXTOR tokamak is the detailed study of fast plasma events at a high spatial resolution and a high repetition rate of the measurements. The diagnostic uses intra-cavity probing of the plasma with a repetitively pulsed ruby laser and a fast CMOS camera as detectors. Since 2004, the TS system on TEXTOR has been gradually and systematically enhanced for the measurements of fast plasma events. For that it has recently been upgraded to obtain a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 25 publications
3
79
0
Order By: Relevance
“…The values of the electron temperature T e are compared by Thomson scattering (TS) diagnostic which measures T e along a central vertical chord. 36 The TS data from the upper and lower plasma edges (∼15 spatial points) were mapped to the high field side region and confirmed the electron temperature from the ECE measurement (not shown here). Phase analysis shows that in this case no coherent component can be found in the signal as expected.…”
Section: Electron Cyclotron Emissionsupporting
confidence: 78%
“…The values of the electron temperature T e are compared by Thomson scattering (TS) diagnostic which measures T e along a central vertical chord. 36 The TS data from the upper and lower plasma edges (∼15 spatial points) were mapped to the high field side region and confirmed the electron temperature from the ECE measurement (not shown here). Phase analysis shows that in this case no coherent component can be found in the signal as expected.…”
Section: Electron Cyclotron Emissionsupporting
confidence: 78%
“…Edge spectroscopy was deployed to investigate the impurity level around the dust holder. Dust particles were detected by the Thomson scattering system (TS) [7] which was used to evaluate electron temperature and density during and immediately after the dust mobilization and to determine the size of remaining dust particles and their temperature. The supersonic helium beam [8] was deployed to investigate electron density and temperature in the vicinity of the last closed flux surface (LCFS).…”
Section: Experimental Planmentioning
confidence: 99%
“…Dependence of the PDI threshold pump power on the microwave beam waist obtained from equation (10) and shown in Figure 5 deserves a few comments. At the small beam waist the inequality 1 T  holds so that the IB wave diffraction losses along the magnetic field line dominate over its radial convective losses, moreover the EB wave poloidal localization region is larger than the PDI pump region when y w   .…”
Section: Threshold and Growth Rate Of The Absolute Pdimentioning
confidence: 98%
“…It was shown that the local maximum of the plasma density, which is usually observed in the O-point of magnetic island at Textor [10], can lead to localisation of the low frequency ion Bernstein (IB) decay wave and thus to suppression of IB wave convective losses in radial direction. A more complicated 2D analysis of the IB wave propagation accounting for the poloidal inhomogenuity of magnetic field in toroidal plasma have shown possibility of IB wave localization in the poloidal direction, as well [11], [12].…”
Section: Introductionmentioning
confidence: 99%